Analisis Nilai-Nilai Pendidikan Karakter Melalui Pendekatan Multikultural pada Kurikulum Pendidikan Dasar Mata Pelajaran Pendidikan Kewarganegaraan di SDN 102 Aneka Marga - Novidayanti M; Khoirun Nisa Hasibuan; Lailatul I’zaati (LP. Ma'arif Janggan Magetan, 2023)
This research aims to explain the effectiveness of character education through a multicultural approach to civic education in elementary schools. Where character education does not have special subjects but character education is still organized by combining into all subjects in elementary school, one of which is the subject of civic education or commonly abbreviated as PPKN. Which is expected that the younger generation in the future will continue to behave in accordance with the philosophy of Pancasila and the 1945 Constitution. Therefore, the next generation of young people are taught character starting from an early age, namely in education at the elementary school level. This research is carried out with a qualitative approach to case study methods. The data collection techniques used are interviews, observations and documentation. Data analysis techniques consist of data reduction, data presentation and inference. While the validity of data uses triangulation methods and time.